Menelisik Dorongan Agresi Para Pelajar Pelaku â€œKlithihâ€ di Yogyakarta - Sarwono, Budi (Program Studi Bimbingan dan Konseling, Universitas Sanata Dharma, 2019)
This paper is a theoretical analysis of aggressive behavior of adolescent in Yogyakarta who has exceeded the limits of reasonableness. This aggression behavior culturally called